Risk information seeking and processing about particulate air pollution in South Korea : the roles of cultural worldview - Kim, Hye Kyung (2019)
This study integrates cultural theory of risk into the risk information seeking and processing model in the context of particulate air pollution in South Korea. Specifically, it examines how cultural worldviews (hierarchy, individualism, egalitarianism, and fatalism) influence the way people interpret risk about an environmental risk, which may in turn promote or deter their information seeking and processing about the risk. An online survey (N = 645) showed that egalitarianism was positively associated with perceptions of societal and personal risks, affective responses toward the risk, and informational subjective norms. Perceived societal risk, in particular, mediated the effect of egalitarianism on information insufficiency. Moreover, cultural worldview was a significant moderator of the relationships between information insufficiency and risk information seeking and processing. The positive relationship between information insufficiency and information seeking grew stronger with increasing egalitarianism. In contrast, the negative relationship between information insufficiency and heuristic processing was strengthened with increasing hierarchy. This study extends prior theories and models in risk communication by addressing the roles of cultural worldview, an important individual difference factor in interpreting environmental risks.